CO photolysis of cytochrome oxidase investigated by ps resonance Raman spectroscopy - Schelvis, Johannes; Deinum, Geurt; Varotsis, Constantinos (My University, 1999)
Low-power picosecond resonance Raman spectroscopy was used to investigate the identity of the axial ligand of heme a3 and relaxation processes in the heme a3 pocket of cytochrome oxidase after CO photolysis. Our results show that the proximal histidine remains ligated to heme a3 after CO photolysis excluding the transient ligation of a photolabile, endogenous ligand. Furthermore, the relaxation of the heme a3 macrocycle modes occurs on the sub ps time scale, while relaxation of the heme pocket to its equilibrium conformation takes place on the μs time scale
Keywords: Cytochrome oxidase; Photochemistry; Raman spectroscopy; Chemistry; Heme; Ligands